Photodynamic therapy for AMD and non-AMD patients: One-year results in Thais - Mansing Ratanasukon (2018)
Objective: To evaluate the effect of photodynamic therapy (PDT) with verteporfin for age-related macular degeneration (AMD) and non-AMD in Thais, and compare with the Treatment of Age-Related Macular Degeneration with Photodynamic Therapy (TAP) and Verteporfin in Photodynamic Therapy (VIP) study. Material and Method: The authors prospectively evaluated all data of 51 eyes of 51 patients who had undergone PDT and accomplished a 1-year follow up. The assessments were divided into two categories: group 1 included three subsets of AMD, and group 2 was non-AMD. The first group classified into three subgroups: group1A: AMD with subfoveal choroidal neovascularization (CNV) and TAP/VIP compatible with recommendation guidelines characteristics, group 1B: AMD with subfoveal CNV and TAP/VIP incompatible, and group 1C: AMD with non-subfoveal CNV. The measurement outcomes comprised of the baseline characteristics, change in visual acuity, and number of treatments. Results: Thirty-eight eyes had CNV-related AMD and 13 eyes were non-AMD. At the 12-month examination, the mean visual acuity change in group 1A, 1B, 1C had increased 0.19 (p = 0.077), 0.14 (p = 0.076), and 0.24 (p = 0.003), respectively. The number of treatments was 1.8 in group 1A, 2.3 in group 1B, and 1.5 in group 1C. Conclusion: PDT is beneficial to Thai patients with AMD at first year, even if they were not compatible with TAP/VIP criteria.